Peran Fatwa DSN-MUI Terhadap Kasus Wanprestasi Nasabah Pada Bisnis Syariah di Indonesia - Fadhil, Muflihul; N, Nurnasrina; Salman, Nola Fibriyani Bte; Huda, Nurul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN MUI) plays a crucial role in addressing issues of default (failure to fulfill agreements) in sharia-based contracts. In Sharia financial transactions, default needs to be resolved fairly and in accordance with Islamic principles, which prohibit elements of riba (unjust enrichment), gharar (uncertainty), and zalim (oppression). (penindasan). The DSN MUI fatwa provides guidance on ta’widh or compensation as a form of recompense for the actual losses suffered by the aggrieved party, unlike fines which are more punitive or seek additional profit. Through this fatwa, DSN MUI encourages adherence to contracts, maintains the balance of rights and obligations, and ensures that the resolution of default is carried out without harming either party. The procedures in this research were carried out in stages, namely collecting library data, reading, taking notes, reviewing, gathering concepts or manuscripts, and then elaborating and explaining the collected data or texts related to the main discussion topic in this research. This article discusses the important role of the DSN MUI fatwa in creating transparency, justice, and adherence to Sharia principles in addressing default, as well as its impact on the integrity of Sharia financial transactions in Indonesia.